Notas para uma cidade por vir: os gestos fílmicos engajados na invenção do espaço urbano - Vieira, Ana Paula Veras Camurça (2021)
From the proposal of a text-path, this research seeks to walk in the company of some films, both fictional and documentary, made in recent years in Fortaleza - CE. During this path, our listening was attentive to the ways in which the images, in the middle of the disputes that emerge on the surface of the urban space, collaborate with a confrontation with the hegemonic projects of the city. Each film elaborates substantial gestures in the reconfiguration of a relationship with the city by affirming a space of invention, questioning the ways of acting of the instituted powers and tensioning certain visibility regimes. Along with the films Duas Avenidas (Diógenes Lopes, 2012), Vista mar (Rubia Mércia, Pedro Diógenes, Rodrigo Capistrano, Victor Furtado, Claugeane Costa and Henrique Leão, 2009), Titanzinho Não Vende (Coletivo Servilost, 2019), VENDO MAR (Collective realization, 2016), Visita Guiada (Victor Furtado, 2016), Ponte Velha (Victor de Melo, 2018), Visita da Raquel Rolnik no Poço da Draga – Parte I (Conselho Comunitário da Defesa Social e Ilha da draga audiovisual, 2012), Mauro em Caiena (Leonardo Mouramateus, 2012) and Boca de Loba (Barbara Cabeça, 2012), in a process that was constituted taking into account the direct implication of the researcher, we approach how these film gestures invent ways of engaging in time and in space.